2023
DOI: 10.3389/fcimb.2023.1197646
|View full text |Cite
|
Sign up to set email alerts
|

The neuromodulatory effects of flavonoids and gut Microbiota through the gut-brain axis

Haoran Wang,
Tingting Zhao,
Zhenjiang Liu
et al.

Abstract: Recent investigations show that dietary consumption of flavonoids could potentially confer neuroprotective effects through a variety of direct and indirect mechanisms. Numerous flavonoids have been shown to cross the BBB and accumulate within the central nervous system (CNS). Some of these compounds purportedly counteract the accumulation and deleterious effects of reactive oxygen species, fostering neuronal survival and proliferation by inhibiting neuroinflammatory and oxidative stress responses. Moreover, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Several studies in animal models have demonstrated that flavonoids reduce oxidative stress, decrease neuroinflammation, stimulate neurogenesis, activate neuronal regeneration, and protect the nervous system through several various mechanisms [ 70 , 71 ]. Some specific flavonoids have the ability to cross the BBB and provide direct neuroprotective effects by inhibiting oxidative stress, reducing inflammatory responses, regulating neuronal metabolism, and promoting neuronal regeneration [ 72 ]. Additionally, some studies suggest that flavonoids can indirectly protect the nervous system by modulating the composition and metabolites of gut microbiota that have an impact on the function of the GBA [ 73 , 74 ].…”
Section: Prevention and Treatment Of Phytochemicals For Gba In Neurod...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in animal models have demonstrated that flavonoids reduce oxidative stress, decrease neuroinflammation, stimulate neurogenesis, activate neuronal regeneration, and protect the nervous system through several various mechanisms [ 70 , 71 ]. Some specific flavonoids have the ability to cross the BBB and provide direct neuroprotective effects by inhibiting oxidative stress, reducing inflammatory responses, regulating neuronal metabolism, and promoting neuronal regeneration [ 72 ]. Additionally, some studies suggest that flavonoids can indirectly protect the nervous system by modulating the composition and metabolites of gut microbiota that have an impact on the function of the GBA [ 73 , 74 ].…”
Section: Prevention and Treatment Of Phytochemicals For Gba In Neurod...mentioning
confidence: 99%
“…The indirect effects of flavonoids, such as their ability to modulate gut microbiota and the GBA, may have a more significant impact than their direct effects on the CNS [ 72 ]. Research has shown that flavonoids have the ability to control the growth of specific bacterial groups and modify the structure and function of gut microbiota [ 75 ].…”
Section: Prevention and Treatment Of Phytochemicals For Gba In Neurod...mentioning
confidence: 99%
“…Experimental results show that flavonoids and their conjugates derivatives may cross the bloodbrain barrier and exert pharmacological action on the central nervous system (Jäger & Saaby, 2011;Youdim et al, 2003) by activating neuronal signaling pathways (Spencer, 2007) and neurotransmitter systems (i.e., serotonergic, GABAergic, noradrenergic, and dopaminergic, among others) involved in neuropsychiatric disorders as anxiety and depression (German-Ponciano et al, 2018;C. Wang et al, 2023;H. Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%